Semantics of set phrases with the colour lexeme “white” in modern English - Vorobyova, I.M. (Харкiвський нацiональний унiверситет iм. В.Н. Каразiна, 2011)
The article deals with semantic peculiarities of set phrases with the colour lexeme “white” in modern English. Cultural linguistics states culture in the language its means and ways of coding cultural information. The fixation of cultural differences is connected with language sings, among which phraseological units are of great importance. It’s especially essential to study active processes of using rethinking and transformary phraseological units with colour names in modern English by taking in account cultural background.
Keywords: phraseology; colour adjective; colour lexeme; phrasal unit